Dark Triad, Aggression and Sensation Seeking - Mitov, Tijana; Gojković, Vesna; Dostanić, Jelena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
This study examined whether personality traits defining the Dark Triad (narcissism, Machiavellianism and subclinical psychopathy) predict the extent and the mode of expression of aggressive behaviour. We also investigated the association between the three Dark Triad traits and sensation seeking, and looked into gender differences across all four traits. To this objective, 144 males and 156 females from Nov Sad, Serbia (mean age 23 years) were administered: Dirty dozen dark triad scale (α = 0.86; Jonason & Webster, 2010), Aggression questionnaire (α = 0.95; Žužul, 1987) and the Sensation seeking scale (α = 0.80; Zuckerman, 1994). All three Dark Triad traits had significant positive correlations with aggressive and violent behaviour, but not with sensation seeking. As expected, subclinical psychopathy was highly predictive of all modes of aggressive behaviour. Contrary to our expectations, subclinical psychopathy did not correlate with sensation seeking. In addition, we found no evidence for an association between aggression and sensation seeking. Discriminant analysis provided evidence that high Machiavellianism, sensation seeking, and aggression were predominantly found among the males. A somewhat unexpected pattern of our results is probably due to our use of a non-clinical sample that is not prone to risk-taking behaviour.